Is maintenance chemotherapy always necessary in gestational trophoblastic neoplasia? A retrospective cohort analysis - Hafızoğlu, Emre; Bardakçı, Murat; Algın, Efnan; Bal, Öznur; Uncu, Doğan (The European Research Journal, 2025)
Objectives: Gestational trophoblastic neoplasia (GTN) is a rare but highly curable group of gestational tumors. Current risk stratification relies on the International Federation of Gynecology and Obstetrics (FIGO) staging and WHO scoring systems, yet both have shown limited accuracy in predicting relapse or chemoresistance. The necessity of routine maintenance chemotherapy following remission - particularly in low-risk patients - remains controversial. Methods: We conducted a retrospective cohort study of 25 patients with GTN treated between 2006 and 2022. Demographic, clinical, and treatment-related data were analyzed. Outcomes of interest included methotrexate (MTX) resistance, relapse, and the use of maintenance chemotherapy. Follow-up duration and disease outcomes were assessed descriptively. Results: The median age at diagnosis was 28 years. Most patients (76%) had FIGO stage I disease; 44% were classified as high-risk. MTX resistance occurred in two patients (8%), both low-risk. Only one relapse was observed, occurring five years after remission. Maintenance chemotherapy was given to 64% of patients. Notably, none of the eight patients who did not receive maintenance therapy - including four high-risk cases - experienced relapse. No clear difference in outcomes was observed between stage I and stage III patients. Conclusions: In this real-world cohort with long-term follow-up, maintenance chemotherapy did not appear necessary to prevent recurrence, even in select high-risk patients. Additionally, the FIGO/WHO systems showed limited prognostic discrimination. These findings support the need for individualized, response-adapted management strategies and underscore the limitations of current risk models in GTN.